Compositional engineering of doped zero-dimensional zinc halide blue emitters for efficient X-ray scintillation. Issue 12 (11th May 2022) - Zhou, Yingchun; Zhou, Quan; Niu, Xiaowei; Yan, Zhengguang; Lin, Taifeng; Xiao, Jiawen; Han, Xiaodong
Abstract : A highly efficient zinc halide scintillator is developed through a compositional engineering strategy. Abstract : Recently, doped ternary zinc halides with high photoluminescence quantum yields (PLQYs) have demonstrated great potential in light emitting applications. However, the composition-dependent photophysical properties of ternary zinc halides have not been investigated, and their X-ray scintillation performances remain unexplored. Here, a compositional engineering strategy for highly efficient Cu + -doped zero-dimensional A2 ZnX4 (A = Rb, Cs; X = Cl, Br) blue emitters is presented. It is found that the A-site cations show a negligible influence on the emission spectra of both pure A2 ZnX4 and Cu + -doped A2 ZnX4, while the change of the halide anion slightly shifts the emission peak of doped A2 ZnX4 . The detailed photoluminescence (PL) studies indicate that the emission of Cu + -doped A2 ZnX4 may come from two self-trapped exciton (STE) emission centers, namely Zn-related and Cu-related STEs. An energy transfer process from the Zn-related STE to the Cu-related STE is proposed. Based on the composition dependent photophysical and scintillation property study, Cu + -doped Cs2 ZnBr4 is found to show the best scintillation performance among these zinc halides. Cu + -doped Cs2 ZnBr4 shows a relatively high light yield of ∼10 000 photons MeV −1, a low detection limit of 57 nGyair s −1, and good radiation stability. The X-ray imaging results based on a doped Cs2 ZnBr4 scintillation screen show a high spatial resolution of up to 9 line pairs per millimeter. These results demonstrate that the doped Cs2 ZnBr4 scintillator could be a potential candidate for sensitive X-ray detection and imaging.